The Effect of Swedish Foot Massage on Reducing Fatigue and Muscle Cramps in Hemodialysis Patients at Royal Prima Hospital - Theresia Marito Siregar; Irfan Ramadhan Sagala; Yitro Dakhi; Elis Anggeria (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Hemodialysis is an alternative treatment for chronic kidney sufferers. Hemodialysis patients often experience fatigue and muscle cramps. One therapy to reduce fatigue and muscle cramps is Swedish massage. The aimed to determine the effect of Swedish foot massage on reducing fatigue and muscle cramps in hemodialysis patients at the Royal Prima General Hospital. The method uses a quasi-experimental with a one-group pre-test and post-test design, using the Wilxocon test. The results on fatigue before the Swedish massage treatment were that 72.2% of respondents experienced fatigue after treatment 97.2% of respondents were not tired. The muscle cramps before Swedish massage treatment, 72.2% of the frequency of cramps every week, 97.2% of the severity was very painful, 100% of the duration lasted 1-10 minutes, and 75.0% of the time the cramps during the day. After the Swedish massage treatment, the frequency of cramps 100% every week. severity level 100% slightly painful, 94.4% cramp duration lasts ≤1 minute, 100% cramp time during the day. Based on p-value fatigue 0.00, frequency 0.02, pain level 0.00, duration 0.00, and time 0.03, there was a significant difference before and after Swedish massage treatment on the legs in reducing fatigue and muscle cramps in hemodialysis patients.